9x-3=10x+3

Simple and best practice solution for 9x-3=10x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x-3=10x+3 equation:


Simplifying
9x + -3 = 10x + 3

Reorder the terms:
-3 + 9x = 10x + 3

Reorder the terms:
-3 + 9x = 3 + 10x

Solving
-3 + 9x = 3 + 10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10x' to each side of the equation.
-3 + 9x + -10x = 3 + 10x + -10x

Combine like terms: 9x + -10x = -1x
-3 + -1x = 3 + 10x + -10x

Combine like terms: 10x + -10x = 0
-3 + -1x = 3 + 0
-3 + -1x = 3

Add '3' to each side of the equation.
-3 + 3 + -1x = 3 + 3

Combine like terms: -3 + 3 = 0
0 + -1x = 3 + 3
-1x = 3 + 3

Combine like terms: 3 + 3 = 6
-1x = 6

Divide each side by '-1'.
x = -6

Simplifying
x = -6

See similar equations:

| 10(d)+5(2d)+50(2d+5)=610 | | 2N+19=2(2(10))+1 | | 2N+19=2(2(4))+1 | | 2x+10=9x-18 | | 8v+26=(-4v-6)-6 | | 10(d)+5(d+2)=115 | | 2N+19=2(20)+1 | | 2N+19=2(9)+1 | | 4+10=3-2 | | 2N+19=2(10)+1 | | F(x)=-5x^2+40x | | 2N+19=2(8)+1 | | 36x+1=73 | | 2N+19=2(2)+1 | | 14x+7=91 | | 2N+19=2(3)+1 | | 2N+19=2(2(3))+1 | | (x+4-3x^2)+(7x+3x^2-5)=0 | | 2N+19=2(2(2))+1 | | 5xy*3y^2= | | 4(2x-5)-11=3x+49 | | x+yz=30 | | 10+4=3-2 | | 3n-3=1.5n+3 | | (x-25)(x-4)=0 | | (1/4)*x-2*x-7/4=0 | | n^2-80=0 | | 2.4+-6.2= | | 2a-1/a=21/10 | | 1269-2/3= | | 2/3-1269= | | -2+-12+9+-6= |

Equations solver categories